Kemampuan Representasi Matematis Siswa SMP melalui Model Pembelajaran Auditory Intellectually Repetition (AIR) - Zaituni; Syamsuddin, Nuralam; Darwani, Darwani (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2026)
Mathematical representation ability is an important skill that students must have in learning mathematics. However, based on the results of observations that researchers have conducted, it can be seen that students' mathematical representation ability has not yet developed optimally. Therefore, it is very important to create active learning in order to improve students' mathematical representation ability. One learning model that is thought to be able to solve the problem of students' mathematical representation ability is the AIR learning model. This study aims to determine the mathematical representation ability of students taught with the AIR learning model. The research method used is a quasi-experimental design with a pre-test-post-test control group design. Sampling in this study was taken by cluster random sampling. The sample consisted of 22 students in the experimental class and 25 students in the control class. The results showed that the mathematical representation ability of students taught with the AIR model was better than the mathematical representation ability of students taught with the conventional learning model.